2021
DOI: 10.3390/healthcare9060648
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Attitudes towards Advance Care Directives (ACDs): An Online Survey of Portuguese Adults

Abstract: (1) Background: Evidence shows that facilitated advance decisions can increase the number of meaningful and valid Advance Care Directives (ACDs) and improve the quality of care when End-Of-Life (EOL) is near. Little is known about the awareness and attitudes of Portuguese adults towards ACDs. The present study aims to assess the knowledge, attitudes, and preferences of a sample of Portuguese adults regarding EOL care decisions and ACDs. (2) Methods: A total of 1024 adults were assessed with an online cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 39 publications
(61 reference statements)
2
7
0
Order By: Relevance
“…It is likely that general public’s’ attitudes towards ADs and ACP may have changed after the outbreak of COVID-19. The COVID-19 pandemic may have highlighted the importance of ADs and ACP due to limited medical resources, [ 40 ] and the public become more aware of the fact that health can deteriorate suddenly and unexpectedly [ 41 ]. Our study showed that only few adults had heard of ADs, but most of them had positive attitudes toward ADs after learning about it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that general public’s’ attitudes towards ADs and ACP may have changed after the outbreak of COVID-19. The COVID-19 pandemic may have highlighted the importance of ADs and ACP due to limited medical resources, [ 40 ] and the public become more aware of the fact that health can deteriorate suddenly and unexpectedly [ 41 ]. Our study showed that only few adults had heard of ADs, but most of them had positive attitudes toward ADs after learning about it.…”
Section: Discussionmentioning
confidence: 99%
“…Policy about ADs/ACP should be made to respect adults’ rights in Mainland China. Online educational materials and social media may be helpful in encouraging EOL discussions and promote ADs awareness under the conditions of the COVID-19 pandemic [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…A low level of knowledge on these directives was observed since only 13.3% of the participants knew about PAD and only 5.0% had previously lled in a PAD. These results are somewhat con icting with the publication from Laranjeira et al, 17 who conducted an online survey on advanced care directives for improving the quality of care on patients at the end of life, including 1024 Portuguese adults, where a signi cant proportion (76.4%) reported having heard of ACP, but only 2.3% had ever lled in these type of directives. These differences might be due to the fact that the participants in that were younger (40.3 ± 11.4 years old) and had a higher proportion of university (or similar) enrolment (79.9%) compared to our sample.…”
Section: Discussionmentioning
confidence: 71%
“…Similar to previous studies examining perspectives regarding advances care planning in general (36,37) and advance directives in particular (38), all participants lacked a clear understanding of the concepts. They tended to conflate advance directives with people's last will or testament, and those in the veteran Jewish and Arab groups even equated them with euthanasia.…”
Section: Understanding Dementia-related Advance Directivesmentioning
confidence: 92%